Dominican Republic (Communications, 2010)
Get all three comprehensive reports bundled into one for a complete media and communications profile of Dominican Republic. An excellent source of practical information, this profile offers an extensive dialing guide with city codes, a listing of ISPs and Internet cafes, profiles of the major media outlets (with contact info!) and more.